Adaptation of Ustilago maydis to phenolic and alkaloid responsive metabolites in maize B73 - Guo, Xuanyue; Yang, Zhen; Zhang, Jinjin; Hua, Juan; Luo, Shihong (Frontiers in Plant Science, 2024)
The adaptation of pathogenic fungi to plant-specialized metabolites is necessary for their survival and reproduction. The biotrophic fungus Ustilago maydis can cause maize smut and produce tumors in maize (Zea mays), resulting in reduced maize yield and significant economic losses. Qualitative analysis using UPLC-MS/MS revealed that the infection of maize variety B73 with U. maydis resulted in increased levels of phytohormones, phenolics, and alkaloids in maize seedling tissues. However, correlation analysis showed that nearly all compounds in the mechanical damage group were significantly negatively correlated with the shoot growth indexes of maize B73. The correlation coefficients of 2-hydroxy-7-methoxy-1,4-benzoxazin-3-one (HMBOA) and maize B73 shoot length and shoot weight were r = -0.56 (p < 0.01) and r = -0.75 (p < 0.001), respectively. In the inoculation group, these correlations weakened, with the correlation coefficients between HMBOA and maize B73 shoot length and shoot weight being r = 0.02 and r = -0.1, respectively. The correlation coefficients between 6-methoxy-2-benzoxazolinone (MBOA) and the shoot weight were r = -0.73 (p < 0.001) and r = -0.15 in the mechanical damage group and inoculation group, respectively. These findings suggest that increased concentrations of these compounds are more positively associated with mechanical damage than with U. maydis infection. At high concentrations, most of these compounds had an inhibitory effect on U. maydis. This study investigated the ability of U. maydis to regulate various compounds, including phytohormones, phenolic acids, and alkaloids in maize B73, providing evidence that U. maydis has adapted to the specialized metabolites produced by maize B73.